Pengaruh Fungsi Manajemen dan Evaluasi Pembelajaran terhadap Prestasi Palang Merah Remaja di SMK Negeri 47 Jakarta - Rismiadi, Yrfan; Sudarman, Enjang; Suhardi, Suhardi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The extracurricular activity of the Youth Red Cross (Palang Merah Remaja/PMR) represents a form of holistic education aimed at developing students’ character and competencies beyond academic learning. However, its effectiveness in enhancing student achievement remains underexplored. This study aims to examine the influence of management functions and learning evaluation on the performance of PMR members at SMK Negeri 47 Jakarta. A quantitative approach was employed, involving 37 PMR student members as the total sample. Data were collected through a structured questionnaire consisting of 30 items and analyzed using multiple linear regression with SPSS version 22. The results show that both management functions and learning evaluation have a significant and positive influence on PMR achievement. The regression equation obtained is Y = 1.994 + 0.359X₁ + 0.660X₂, with a determination coefficient (R²) of 0.908, indicating that 90.8% of the variance in PMR performance is explained by the two independent variables. The t-test and F-test further confirm the partial and simultaneous significance of both predictors. Among them, learning evaluation contributes more strongly. The findings suggest that effective management and systematic evaluation are crucial to supporting extracurricular success in youth humanitarian programs.